Effect of Probiotic Supplementation on Maternal Depression, Anxiety and Attachment in Gestational Diabetes by Improving Mediterranean Diet Quality: A Randomized Controlled Trial - Fatma Bengü Kuyulu Bozdoğan; Seray Kabaran; Aybala Tazeoğlu (Clinical and Experimental Obstetrics & Gynecology)
Background: Factors such as the coronavirus disease 2019 (COVID-19) pandemic quarantine, economic decline, and unemployment have an impact on mental health, and have made mental illnesses an important public health problem worldwide. According to the World Health Organization, depression is currently the fourth reason of the global burden of diseas. Evidence shows that women with gestational diabetes (GDM) are at higher risk of developing depression during pregnancy. Despite extensive research carried out by the probiotic industry in recent years, there is a lack of consensus on the available evidence on how best to use probiotics in mental health. Considering the impact of probiotics on mental health, our study aimed to answer the question of whether probiotic supplementation is effective on depression and anxiety in women with gestational diabetes. Methods: In this randomized controlled study with an allocation ratio of 1:1, the participants were divided into two groups: control group, received standard diet compatible with Mediterranean diet (MD) while the probiotic supplementation group received both the standard diet compatible with MD and probiotic supplementation (Lactobacillus acidophilus, Lactobacillus rhamnosus, Bifidobacterium bifidum, Bifidobacterium longum and Enterococcus faecium). The participants’ sociodemographic data, medical history, pregnancy data, and adherence to the Mediterranean diet at 24 and 36 weeks of pregnancy were recorded. Edinburgh Postnatal Depression Scale (EPDS), Pregnancy-Related Anxiety Scale (PrAS), and Maternal Antenatal Attachment Scale (MAAS) scales were used. Two-way repeated measures analysis of variance was used to examine group and time effects and group-time interactions. Additionally, sleep problems, stressful events, and sedentary physical activity were added as exclusion criteria to optimize the impact of potential problems on depression. Results: In the control and probiotic groups, anxiety scores at 36 weeks of gestation were found to be 16.53 ± 3.49 and 16.27 ± 3.62, respectively (p = 0.771). Maternal attachment scores at 36 weeks of gestation were found to be 67.39 ± 7.56 and 69.29 ± 5.89 in the control and probiotic groups, respectively (p = 0.266). Depression (8.24 ± 2.48; 8.56 ± 2.75, p = 0.627) and anxiety scores during pregnancy and weight gain (12.80 ± 2.97 and 12.07 ± 2.41, p = 0.284) were lower in the probiotic supplementation group at 36 weeks of gestation compared to the control group. The Mediterranean diet score was higher in the probiotic supplement group (33.64 ± 4.92) compared to the control group (31.97 ± 5.18) at week 36. Multiple regression analysis was performed to examine the prediction of depression risk based on the scores obtained from the Med-diet (Mediterranean diet) scale. Accordingly, EPDS (β = –0.57, p = 0.001), PrAS (β = –0.32, p = 0.004), and MAAS (β = 0.78, p = 0.003) significantly predicted the Med-diet score. A one-unit improvement in the Med-diet score resulted in a decrease of 0.57 units in depression, a decrease of 0.3 units in anxiety and an increase of 0.78 units in maternal attachment in both groups. Conclusions: In GDM, the Mediterranean diet quality had a significant negative relationship with depression and anxiety, and a positive relationship with maternal attachment. The group receiving probiotic supplementation had lower scores for depression and anxiety and lower gestational weight gain. However, the Mediterranean diet score was higher in the probiotic group at week 36. Clinical Trial Registration: Registered under ISRCTN registry (https://www.isrctn.com/ISRCTN96215615) identifier no. ISRCTN96215615.